The Effect of Isometric Forearm Contraction Exercises Added to Elderly Gymnastics on Blood Glucose Levels and Blood Pressure Among Older Adults in Kebumen - Asifa Maura Salsabila; Moh. Ali Imran; Tri Laksono (Jurnal Sehat Indonesia (JUSINDO), 2026)
The global elderly population continues to rise, with Indonesia ranking fourth worldwide. The increasing number of older adults is accompanied by a rising prevalence of non-communicable diseases such as hypertension and diabetes mellitus. In the Mutiara Sari Kebumen Elderly Community (34 members), low physical activity levels have been observed, increasing vulnerability to these health problems. Therefore, appropriate interventions are needed to help reduce blood sugar levels and blood pressure through the activation of regular physical activity. This study aimed to determine the effects of elderly gymnastics with and without isometric handgrip exercises on blood sugar levels and blood pressure, as well as to compare the effectiveness of the two interventions among elderly members of the Mutiara Sari Kebumen community. This research employed a quasi-experimental pre-test and post-test control group design. The study subjects were 34 elderly individuals aged 60–74 years, selected using a total sampling technique. Participants followed an exercise program five times per week for four weeks. Instruments used included the Easy Touch GCU device and a sphygmomanometer. Data were analyzed using descriptive statistics, normality and homogeneity tests, and hypothesis testing. Paired Sample T-Test results showed significant effects in both groups (p = 0.000; p < 0.05). However, Independent Sample T-Test results indicated no significant difference between the two interventions in reducing blood sugar and blood pressure. Both elderly gymnastics alone and in combination with isometric handgrip exercises effectively reduced blood sugar levels and blood pressure, with no significant difference between the two interventions